The relationship between sexual function and emotional intelligence and its components based on fertility status in women referring to health centers in Yazd - Mahshid Bokaie; Zohre Ahmadi; Marzie Reisi; Leila Asadi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Sexual function is affected by many psychological factors and emotions. The impact of emotion management varies in different fertility situationsThis can affect women's sexual function. Therefore, the aim of this study was to investigate the relationship between sexual function and emotional intelligence and its components based on fertility status in women referring to health centers in Yazd. MATERIALS AND METHODS: The present study is a correlational study that was performed on 165 women with inclusion criteria and referred to 4 selected health centers in Yazd in 2017. The study tools include demographic questionnaire, Female Sexual Function Index sexual function, and Bar-On emotional intelligence. The fertility status of women in the present study included a history of infertility, number of children, and history of abortion. The analysis was performed using descriptive statistical methods and analytical tests with SPSS software version 18. RESULTS: The mean score of all components of emotional intelligence except the components of self-expression, independence, and emotional self-awareness and also the total score of emotional intelligence infertile people was significantly higher than infertile people (P < 0.05). Regarding the relationship between emotional intelligence and sexual function in terms of fertility variables, a significant correlation was observed between the mean scores of all components of emotional intelligence except interpersonal relationships, flexibility, responsibility, empathy, and self-expression with sexual performance score in fertile individuals.(P = 0.000). Conclusion: As a result, it is suggested that the institutions in charge of women's affairs try to increase emotional intelligence and improve women's sexual function by holding workshops and classes for women, especially in women with infertility, childlessness, and history of abortion.